Air quality monitoring system (front-end) using FPGA - Taip, Mohammad Shamsul (2009)
This thesis presents development of Air Quality Monitoring System that might helps government or any industries to monitor the amount of poisonous gases or air pollutants emitted in the air in order to have a safe environment. This system focuses on the development of Graphical User Interface (GUI) menu for user to activate certain sensors and display the results on FPGA (Field Programmable Gate Array) Development Board. The output from sensor circuit acts as input to the FPGA board. The FPGA, which is programmed by using VHSIC hardware description language (VHDL) code, displays the sensor’s output thru LED and seven segment display.